Arthroscopic excision of intraarticular subperiosteal osteoid osteoma of talar neck: A case report - Özdemir, Bülent (Jt Dis Relat Surg, 2020)
Osteoid osteoma (OO) is a benign, small, and painful tumor typically seen in the subcortical shaft and metaphysis of the long bones of the lower limb. The occurrence of this type of tumor on the talar neck is rare and may cause limitation of range of motion of the ankle joint. In this article, a 17-year-old male patient had ankle pain and limitation of joint motion accompanied by synovitis. The OO in the intraarticular subperiosteal talar neck was successfully excised arthroscopically and the nidus was completely removed. The diagnosis was confirmed histopathologically in the postoperative period. In this case, we achieved a successful result with surgical treatment of benign bone tumor in the talus with intraarticular excision of the lesion arthroscopically.